Combined effects of powdered oyster shell (Ostreidae) and lemongrass (Cymbopogon citratus) as a feed additive for growth development of quail (Coturnix coturnix japonica) - Florieza Mangubat; Cerela Looc; Fretzel Mad (Vietnam Journal of Science, Technology and Engineering, 2023)
Calcium, obtained from various sources, is essential to fulfil the dietary requirements of birds. Oyster shells are excellent sources of calcium and are widely used in bird diets. Calcium is a critical factor in eggshell deterioration, affecting its absorption. Consequently, this study aimed to determine the combined effects of powdered oyster shell and lemongrass on the growth, development, and egg quality of birds, specifically using 5, 10, and 15 grams of oyster shell powder as a calcium source. A completely randomised design was used to assess the efficacy of varying amounts of powdered oyster shell. Results revealed that there was no significant change in growth development at different inclusion levels of oyster shell powder and lemongrass solution. However, egg quality exhibited a significant variance at different inclusion levels of oyster shell powder. Similarly, lemongrass solution as a supplement for laying quails demonstrated a significant difference. Therefore, supplementing the calcium source with a blend of 15 g of oyster shell powder and 300 ml lemongrass solution enhanced egg performance and eggshell quality of laying quail by 5%.